Rancang Bangun Aplikasi Mobile Perantau Minang Berdomisili Di Kota Manado Dengan Metode Cluster Analysis - Zalmi, Wahyuni Fithratul; Syahputra, Rendy; Nugraha, Mahendra Kusuma (Universitas Labuhanbatu, 2025)
Applications are software developed to process data and generate information. There are three types of applications, namely desktop applications, web applications, and mobile applications. Mobile applications allow users to access information and resources anytime and anywhere, as long as connected to the internet. Minang nomads are Minangkabau people who live outside West Sumatra, both in Indonesia and abroad. In the city of Manado, Minang nomads often find it difficult to obtain accurate information, such as the number of Family Cards, ethnic or clan groupings, and other important information such as address, occupation, account number, and blood type. With this application, the data of Minang nomads can be centralized and make it easier for them to share information. This application aims to improve relations between fellow Minang nomads in Manado City and strengthen the local economy. Some of the main features of this application include the ease of finding information on the schedule of activities, the number and grouping of tribes, addresses, blood types, as well as the work of Minang nomads.